2012
DOI: 10.1089/ten.tea.2011.0707
|View full text |Cite
|
Sign up to set email alerts
|

Substrate Stiffness Modulates Gene Expression and Phenotype in Neonatal CardiomyocytesIn Vitro

Abstract: Biomaterials to be used as cell delivery systems for cardiac tissue engineering should be able to comply with cardiac muscle contractile activity, while favoring cell survival and neo-angiogenesis in a hostile environment. Biocompatible synthetic materials can be tailored to mimic cardiac tissue three-dimensional organization in the micro- and nanoscales. Nonetheless, they usually display mechanical properties that are far from those of the native myocardium and thus could affect host cell survival and activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
81
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 97 publications
(86 citation statements)
references
References 54 publications
5
81
0
Order By: Relevance
“…Interestingly, CMs seeded on softer substrates in the range of 0.91 -0.08 and 1.53 -0.16 MPa were mostly mature and had assembled sarcomeres. 33 On the contrary, the CMs grown on the stiff PCL (49.67 -2.56 and 133.23 -8.67 MPa) expressed immature cardiac cell genes (Nkx-2.5) and proteins (GATA-4), in addition to a number of genes involved in inflammatory processes. This confirmed the hypertrophy that the differentiation of CM phenotypes is influenced by the substrate stiffness showing that softer substrates induce a more mature phenotype.…”
Section: Fig 1 Micromechanical Loading In Cardiomyocytes (Cms) (A)mentioning
confidence: 96%
See 1 more Smart Citation
“…Interestingly, CMs seeded on softer substrates in the range of 0.91 -0.08 and 1.53 -0.16 MPa were mostly mature and had assembled sarcomeres. 33 On the contrary, the CMs grown on the stiff PCL (49.67 -2.56 and 133.23 -8.67 MPa) expressed immature cardiac cell genes (Nkx-2.5) and proteins (GATA-4), in addition to a number of genes involved in inflammatory processes. This confirmed the hypertrophy that the differentiation of CM phenotypes is influenced by the substrate stiffness showing that softer substrates induce a more mature phenotype.…”
Section: Fig 1 Micromechanical Loading In Cardiomyocytes (Cms) (A)mentioning
confidence: 96%
“…This confirmed the hypertrophy that the differentiation of CM phenotypes is influenced by the substrate stiffness showing that softer substrates induce a more mature phenotype. 33 Furthermore, the effect of substrate stiffness on CM beating has also been investigated, 16 by seeding CMs, derived from embryonic (day 8) chicks, on PA gel substrates of different stiffness for 1-5 days. The PA gel substrates that were considered had a stiffness of 1, 18, and 50 kPa.…”
Section: Fig 1 Micromechanical Loading In Cardiomyocytes (Cms) (A)mentioning
confidence: 99%
“…They noted that neurogenic differentiation was optimal at a stiffness of 0.1-1 kPa, myogenic differentiation at 8-17 kPa and osteogenic differentiation at 25-40 kPa. Several subsequent studies have shown how substrate stiffness affects several different cell types, including neuronal cells [134,135], chondrocytes [136], cardiomyocytes [137,138], dermal fibroblasts [139] and limbal stem cells [140]. Recently, Trappmann et al [141] suggested that substrates of different stiffness have differing protein anchorage densities and configurations that regulate stem cell fate through the mechanical feedback of cells attached to anchored proteins [141].…”
Section: Influence Of the Hydrogel On Cell Behaviourmentioning
confidence: 99%
“…28,29 The responsiveness of adult and undifferentiated cells to substrate stiffness and topology has been the subject of a number of investigations so far, showing that cell-specific responses can be triggered by the mechanics of the substrate. 12,20,30,41,42 Moreover, a specific response of tissue resident cardiac progenitor cells to substrate mechanical properties has been highlighted. 25,43 Recently, cell sensitivity to substrate composition has been associated with the ability of the Hippo pathway downstream effectors YAP and TAZ to act as transcriptional coactivators directly binding to lineage-specific effectors, thus acting as onÀoff relays in mechano-transduction.…”
Section: Articlementioning
confidence: 99%